Cost-benefit analysis of tobacco consumption in Peru - Ríos, Carlos de los (2020)
The purpose of this study is to estimate the distributive effects of tobacco tax increases using the extended cost benefit analysis developed by Fuchs and Meneses (2017), which, in addition to the direct, short-term effects associated with decreased cigarette use, incorporates medium-and long-term effects of reduced cigarette smoking in terms of avoided medical expenses and increase in working years. -- Introduction